Surtain Herbicide Programs for Weed Management in Corn - Patrick W. Geier; Sarah H. Lancaster (Kansas Agricultural Experiment Station Research Reports, 2025)
All herbicides evaluated provided good control of velvetleaf and Russian thistle at Garden City, and did not differ between treatments. Although slight differences occurred among treatments for kochia control, all herbicides provided at least 90% control early and late in the season. Surtain plus Armezon, atrazine, and glyphosate applied early postemergence (EPOST) as well as Surtain applied preemergence (PRE) followed by Armezon Pro, atrazine, and glyphosate postemergence (POST) or Status plus Zidua SC and glyphosate POST were the most effective herbicides for Palmer amaranth and johnsongrass control. At Manhattan, Palmer amaranth control did not differ between treatments at any rating date (98% to 100%). Storen PRE followed by Halex GT was slightly less effective on common sunflower early in the season, but control was nearly complete later in the season. By the end of the season, both Acuron or Storen PRE followed by Halex GT were less effective on entireleaf morningglory at Manhattan. The EPOST treatments of Surtain caused 20% corn necrosis at both locations, but injury did not persist. All herbicides increased yields relative to the untreated controls at both locations, but the difference between treatments only occurred at Garden City.
Keywords: tank mixtures; residual control